Missense variants in TAF1 and developmental phenotypes: Challenges of determining pathogenicity. Issue 2 (25th November 2019) - Cheng, Hanyin; Capponi, Simona; Wakeling, Emma; Marchi, Elaine; Li, Quan; Zhao, Mengge; Weng, Chunhua; Piatek, Stefan G.; Ahlfors, Helena; Kleyner, Robert; Rope, Alan; Lumaka, Aimé; et al.
Abstract: We recently described a new neurodevelopmental syndrome (TAF1/MRXS33 intellectual disability [ID] syndrome) (MIM# 300966) caused by pathogenic variants involving the X‐linked gene TATA‐box binding protein associated factor 1 ( TAF1 ), which participates in RNA polymerase II transcription. The initial study reported 11 families, and the syndrome was defined as presenting early in life with hypotonia, facial dysmorphia, and developmental delay that evolved into ID and/or autism spectrum disorder. We have now identified an additional 27 families through a genotype‐first approach. Familial segregation analysis, clinical phenotyping, and bioinformatics were capitalized on to assess potential variant pathogenicity, and molecular modeling was performed for those variants falling within structurally characterized domains of TAF1. A novel phenotypic clustering approach was also applied, in which the phenotypes of affected individuals were classified using 51 standardized Human Phenotype Ontology terms. Phenotypes associated with TAF1 variants show considerable pleiotropy and clinical variability, but prominent among previously unreported effects were brain morphological abnormalities, seizures, hearing loss, and heart malformations. Our allelic series broadens the phenotypic spectrum of the TAF1/MRXS33 ID syndrome and the range of TAF1 molecular defects in humans. It also illustrates the challenges for determining the pathogenicity of inherited missense variants, particularly for a gene mapping to chromosome X. Abstract : Phenotypes associated with TATA‐box binding protein associated factor 1 (TAF1) variants show considerable pleiotropy and clinical variability, but prominent among the previously unreported effects were brain morphological abnormalities, seizures, hearing loss, and heart malformations. Our allelic series broadens the phenotypic spectrum of the TAF1/MRXS33 intellectual disability (ID) syndrome and the range of TAF1 molecular defects in humans.